Possibilidade de supressão dos direitos sociais com a vinda da reforma trabalhista - Correia, Claudiery Bwana Dutra (2021)
Approved on July 13, 2017, Law No. 13,467, entitled “Labor Reform”, came into force in the Brazilian legal system with the aim of modifying and adding new provisions to the Consolidation of Labor Laws. The justification for this is that the celetist norm would be losing its value, since it was no longer following the changes that occurred in society. According to its own creators, relations would have changed in such a way that there was a mismatch between reality and the Consolidation of Labor Laws, however, latent legal uncertainty is noticeable, since the negative effects of the reform are unquestionable. In view of this, the present work aims to address the aforementioned law, to bring the main points of change of this law and how the jurists have been positioning themselves in this respect, mainly in relation to the main criticisms that have been emerging in this sense, in addition to analyzing whether the This reform is linked to Social and Economic Rights. Regarding the division of labor, at first, it took care to address the general aspects of labor law, where an analysis was made of the before and after labor reform, addressing important points related to historical and evolutionary criteria of labor law. work in Brazil; in turn, in the second moment it was presented how the State has been intervening, currently, in economic relations. The intention was to find out if the labor reform that was once adopted is complying with the principles inherent to Human and Social Rights; and, finally, in the third moment, the impacts that the labor reform has been producing, both for the worker and for the employer, linked to the Economic Law. For this purpose, the deductive method was used, since it sought to present how the phenomenon occurs, and through the bibliographic review carried out on books, documents or any other source, whether printed or virtual, which contributed to the theme, so that, at the end, the reader can understand the proposed theme and carry out the appropriate criticisms pertinent to the subject. As it is a considerably new law, its consequences in practical life are still under construction, and a definitive conclusion is not possible.